KEKURANGAN APARATUR SIPIL NEGARA MENDORONG GUBERNUR BERJUANG MINTA TAMBAHAN - Raudah Mahmud (Prodi Ilmu Administrasi Negara, 2018)
The aim of this research is to know the effort of the Governor of North Kalimantan to improve the quality of the aparatus and the quantity of them .The Location of the research is in Bulungan in 2016/2017.The researcher has the results as follows,(1)The Governor of North Kalimantan without fatique to improve the quality and the quantity of tthe aparatus here,(2)The Governor of North Kalimantan improve the aparatus by sending to the course and training as weel as education,(3)The Governor of East Kalimantan is willingly to make any effort to develop this province to make the same level compared with the other provinces.The suggestions of the researcher are (1)The staff has to partisipate and the efforts of the Governor of the North Kalimantan,(2)The recruitment has to be objective and profesional,(3)The Governor of North Kalimantan has to empower the local people here,(4)The Governor of North Kalimantan has to enforce tthe area to be good governance.